Neonatal Solitary Intestinal Myofibromatosis - Rachida Laamiri; Nahla Kechiche; Meriem Braiki; Rim Hadhri; Lassaad Sahnoun; Mongi Mekki; Mohsen Belghith; Abdellatif Nouri (EL-Med-Pub, 2018)
Solitary intestinal myofibromatosis (SIF) is a very rare condition affecting the pediatric population and carries good prognosis following adequate management based on segmental resection. We describe a rare case who presented with features of neonatal intestinal obstruction due to a solitary stenosing fibrotic lesion originating from the ileum and compatible with SIF.